Legal Protection Model for Victims of Illegal Investment Crimes - Agus Susanto; Fenty U. Puluhulawa; Dian Ekawaty Ismail (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to analyze and construct a model of legal protection for victims of illegal investment crimes. This research is a type of normative research using several approaches, namely the statute approach, case approach, and conceptual approach. The analytical technique used in this study is using analytical descriptive techniques. The results showed that the legal protection model for victims of illegal investment is to reform the Money Laundering Law with an asset recovery approach to the Corruption Eradication Law. The concept contained in Article 18 of the Corruption Eradication Law is an additional crime that can be conceptualized in the provisions of the Money Laundering Law.